Primary multiple peritoneal hydatid cysts in 12 years old child - Menawar Dajenah; Anessa Thabet; Faisal Ahmed; Qasem Alyhari; Abdu Al-hajri; Waleed Aljbri (Elsevier, 2022)
The hydatid cyst (HC) is a parasitic infection produced by cysts comprising Echinococcus granulosus larval stage. It is higher in rural areas in some underdeveloped countries, Yemen. Primary peritoneal and mesenteric HC are uncommon without a precise mechanism of manifestation. Hence, we report a 12-year-old boy was presented with recurrent abdominal pain and gradual growth of abdominal mass in the last three months. Abdominal Computed tomography confirmed three large calcified lesions (one in the left hypochondrium, one in the right and midabdominal region, and the last one in the pelvis, which caused a pressure effect on the urinary bladder). Surgical excisions were made, and the patient left the hospital with oral medication on the sixth postoperative day. Pathological specimen examinations confirmed cystic hydatidosis. In conclusion, primary peritoneal and mesentery HCs are rare. In the case of abdominal mass, HC must be considered in the differential diagnosis, particularly in endemic areas.